Comité Editorial (Revista de Historia, 2025)
Consejo EditorialMaiten Franco y Gastón MontesinoDirectoresConsejo de EdiciónAndrea Rodríguez (Universidad Nacional del Comahue); Rocio BelénMartínez (Universidad Nacional del Comahue) Rolando Bonato(Universidad Nacional del Comahue); Marta Flores (Universidad Nacionaldel Comahue); Sabrina Aguirre (Universidad Nacional del Comahue);Cecilia Allemandi (Universidad Nacional del Comahue).Secretaría de EdiciónGastón Montesino (Universidad Nacional del Comahue)Comité AcadémicoOmar Acha (Universidad de Buenos Aires – CONICET), Argentina; SamuelAmaral (Universidad Nacional Tres de Febrero), Argentina; Waldo Ansaldi(Universidad Nacional de La Plata), Argentina; Susana Bandieri(Universidad Nacional del Comahue – CONICET), Argentina; Marta Bonaudo(Universidad Nacional de Rosario – CONICET), Argentina; Atilio Boron(FLACSO), Argentina; Gerardo Caetano (Universidad de la República),Uruguay; Lila Caimari (Universidad de San Andrés), Argentina; GuillermoMira Delli-Zotti (Universidad de Salamanca), España; Orietta Favaro(Universidad Nacional del Comahue), Argentina; Enrique Mases(Universidad Nacional del Comahue), Argentina; María Estela Spinelli(Universidad Nacional del Centro de la Provincia de Buenos Aires),Argentina; Maristella Svampa (Universidad de Buenos Aires – CONICET),Argentina; César Tcach (Universidad Nacional de Córdoba – CONICET),Argentina; Sergio Grez Toso (Universidad de Chile), Chile.